Recovery of Total Chromium from Tannery Wastewater by Carbonization Application - P E Ochoa; S L Gavilánes; J S Achote; M A Albán (ESPOCH Congresses, 2023)
A carbonization process was carried out for the recovery of chromium from wastewater by chemical treatment with sodium hydroxide as a basic solution in contact with the precursor material at different concentrations [1:0.15 (%w/w) - 1:0.20 (%w/w)]. The physical treatment was carried out with carbonization at 700○C for a period of 2 hours. The obtained samples were characterized by elemental analysis, thermogravimetric analysis (TGA), Fourier transform infrared spectroscopy (FT-IR), atomic absorption spectroscopy, and surface area analysis (BET) to validate the evidence of metal recovery. The results indicate that the percentage of total chromium recovery was 47.62% with respect to the uncarbonized material, establishing that the best carbonization variables are at 700○C and concentration 1:0.20% w/w for 2 hours.